2020
DOI: 10.1186/s12912-020-00500-3
|View full text |Cite
|
Sign up to set email alerts
|

Objective structural clinical examination for evaluating learning efficacy of Cultural Competence Cultivation Programme for nurses

Abstract: Background Culture serves as an adhesive to bind the lives of people. There are no objective, useful tools to assess cultural competence and practice. In this study, we evaluated whether the cultural competence of nurses was strengthened through the Cultural Competence Cultivation Programme. Methods A quasi-experimental research design was used to evaluate nurses working at a medical centre in Taiwan. They were randomly allocated into an experimental group (n = 47), which received the Cultural Competence Cult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…They also found that those who had not participated in the SDM training could also complete the tasks. Our results were also similar to those of Lee et al [ 21 ]. In their study, the experimental group received a cultural-competence cultivation program and the control group did not receive any interventions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…They also found that those who had not participated in the SDM training could also complete the tasks. Our results were also similar to those of Lee et al [ 21 ]. In their study, the experimental group received a cultural-competence cultivation program and the control group did not receive any interventions.…”
Section: Discussionsupporting
confidence: 93%
“…In their study, the experimental group received a cultural-competence cultivation program and the control group did not receive any interventions. Both groups completed the OSCE assessment after the intervention, and although the average score of the experimental group was slightly higher than that of the control group, the difference was not significant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider that cultural competence is not a checklist, and it should evolve as practitioners navigate their fields. 19,20 Doing this work in the classroom allows for inclusivity and individualization to be carried into professional practices, though it is not the only opportunity for exposure. Collaboration amongst pharmacy programs would allow comparison of techniques used, the effect of these interventions on the inclusion of social identities, and student perceptions or knowledge-gained by students.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing as a professional and professional staff with the largest number of service personnel in health services (60% to 70% of the composition of the hospital workforce), of course, must be supported by strengthening the quality both at the formal and informal education levels and oriented to the needs of the community according to the development of culture and civilization. Nursing education is education in the applied Sciences category, which is an integration of nursing knowledge, attitudes and skills through real experience in clinical learning(1) (2). The clinical learning process includes the transformation of nursing science, teaching nursing skills and role models to nurse administrators, especially beginners who requires good, comfortable interpersonal relationship competences and creates mutual respect and trust and satisfaction of the learning process which has an impact on the quality of learning outcomes for student nurse or new nurse (3).…”
Section: Introductionmentioning
confidence: 99%